Online Grammar Learning: How the Learners Perceive its Effectiveness - Oktaviani, Amanda; Setiamunadi, Antonina Anggraini (IJET (Indonesian Journal of English Teaching), 2023)
The pandemic forced all learning to be done online using technologies that can connect students and teachers in different locations. This online teaching and learning also needs to be applied to the teaching and learning of English grammar which is usually much more comfortable to be done offline. This study was conducted to find out university students' perception about the effectiveness of their online grammar learning and their reasons to say that their online grammar learning is effective or ineffective. The data were collected by using a questionnaire to 35 university students of batch 2017, 2018, and 2019. The findings revealed that the most of the students (68.57%) perceived that the online grammar learning is not effective. The reasons are that they could not understand the materials easily when they learnt it online (65.71%), they could not interact with other friends to learn together (54.29%), they could not get grammar corrections from the teachers directly in online learning (37.14%), and they could not follow teachers' grammar explanation easily (37.14%). Besides that, the requirements that they needed to fulfill to use the applications for their online learning also becomes another problem in their grammar learning such as the applications used needed strong internet connections (65.71%), the applications required the students to have a large storage capacity in the device that they used for grammar learning (31.43%), and the applications required the students to have more than 1 gigabyte of internet quota (25.71%).